ANALISIS MOTIVASI BELAJAR PESERTA DIDIK KELAS X PROGRAM LINTAS MINAT PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 16 PALEMBANG - Gita Frimar Lesi Ayu; Dewi Koryati; Riswan Jaenudin (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
This study aims to determine the level of learning motivation of students in class X across cross-interest programs on economic subjects at Palembang State High School 16. This study used a descriptive method where the subjects in this study were students of class X MIPA which amounted to 52 students. Data collection techniques used were questionnaires and interviews. Data analysis techniques were scored based on the rating scale. Based on the results of data analysis, it can be seen that students' learning motivation in economic subjects cross-interest programs in Palembang State High School 16 influenced by intrinsic factors of 74.23% in (high category) and extrinsic at 79.78% at ( high category). Researchers suggest that teachers motivate students more cross-interest programs in growing successful desires while learning economic subjects.